The time-frequency dependence of unemployment on real input prices: a wavelet coherency and partial coherency approach. Issue 10 (25th February 2020) - Meng, Xiangcai
ABSTRACT: While the dependence of unemployment on real oil price and real interest rate is an important issue that has been addressed only in the time dimension, little is known about the movements of real input prices and their impact on unemployment in the time-frequency space. With a continuous wavelet coherency and partial coherency approach and monthly data of Japan and US from January 1960 to May 2017, this paper contributes to the literature by examining the characteristics of the dependence of unemployment on real input prices across frequencies and over time. The empirical results indicate that: First, a rise in real oil price leads to productivity growth slowdown and unemployment increase at the scale of 16–64 months after 1990 for Japan and 8–24 months after 2005 for US. Second, an increase in real interest rate results in higher unemployment at the 16–32-month scale before 1974 for Japan and 8–64-month scale before 2000 for US. Third, the degree of integration between labour market and energy market in US is higher than that in Japan. This study provides time-frequency evidence to the supply side hypothesis about the relationships between input prices and unemployment.